Improving Mathematical Literacy Ability and Learning Independence of SDN 29 Pardomuan 1 Students through the Application of Realistic Mathematics Learning Approaches - Resti Haryanti Sidebang; Muhammad Amin Fauzi; Sendi Ramdhani (Didaktika: Jurnal Kependidikan, 2024)
This research was motivated by the low level of mathematical literacy skills and student independence at school. The focus of the problems studied in this research includes 1) Students' mathematical literacy abilities; 2) Student learning independence; 3) Realistic Mathematics Learning Process; 4) Increasing students' mathematical literacy skills and learning independence in the experimental class and control class; 5) The influence of PMR on students' literacy skills and learning independence in the experimental class. The research method used is quasi-experimental, pretest posttest type. The research population included all fifth-grade students at SDN 29 Pardomuan. The treatment given to the experimental class was Building Space learning using a Realistic Mathematical Approach model. Data analysis was carried out using quantitative analysis. The results of data calculations through statistical tests obtained 1) There is a positive (unidirectional) influence between the Educational Learning Model on Mathematical Literacy Ability with the Sig. Educational Learning Model value (0.000) < 0.05 and the calculated t value (3.838) > t table (1.995); 2) There is a positive (unidirectional) influence between the Educational Learning Model on Student Learning Independence and the Sig. Educational Learning Model (0.000) < 0.05 and calculated t value (4.487) > t table (1.995); 3) There is a positive (unidirectional) influence between the Educational Learning Model on Mathematical Literacy Ability and the Sig value. Educational Learning Model (0.000) < 0.05 and calculated t value (3.838) > t table (1.995); 4) There is a positive (unidirectional) influence between the Educational Learning Model on Student Learning Independence with the Sig. Educational Learning Model value (0.000) < 0.05 and the calculated t value (4.487) > t table (1.995).